Evaluation of Self-Collected Versus Health Care Professional (HCP)-Performed Sampling and the Potential Impact on the Diagnostic Results of Asymptomatic Sexually Transmitted Infections (STIs) in High-Risk Individuals - Simon Weidlich; Sven Schellberg; Stefan Scholten; Jochen Schneider; Marcel Lee; Kathrin Rothe; Nina Wantia; Christoph D. Spinner; Sebastian Noe (MDPI AG, 2023)
Sexually transmitted infections (STIs) are increasing among men who have sex with men (MSM). Screening can improve the detection and outcome of asymptomatic STIs in high-risk populations. Self-sampling may be a resource-optimized strategy; however, its diagnostic reliability compared to testing by healthcare professionals (HCPs) requires further investigation. In this prospective, multicenter cohort study in a high-income country, asymptomatic MSM with a sexual risk profile for STIs were included. Sequential swabs for STI nucleic acid-based diagnosis of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) were performed after randomization, either through self-sampling or HCP-performed sampling. Baseline demographic information, sexual risk behavior, and acceptance and feedback on self-sampling were recorded using an electronic questionnaire. Out of 236 asymptomatic MSM, 47 individuals (19.9%) tested positive for CT and/or NG through self- or HCP-performed sampling. For CT, the sensitivity was 93.3% for both sampling methods, while for NG, it was 90.0% for self-sampling and 95.0% for HCP-performed sampling. Our study demonstrates that self-sampling for asymptomatic STIs has a comparable diagnostic outcome to HCP-performed sampling, with high acceptance in high-risk MSM.